Dr M's race rhetoric unwarranted: Academicians say his words undermine the policies introduced during his 22-year tenure - Abdullah Sani, Asrul Hadi (Malay Mail, 2012)
ACADEMICIANS questioned the logic behind Tun Dr Mahathir Mohamad's statement yesterday that all Malaysians were racists, stressing that by doing so, the former prime minister had actually undermined policies introduced during his 22-year tenure.